The Role of Urban–Rural Connections in Building Food System Resilience - Berkhout, Ezra D.; Sovová, Lucie; Sonneveld, Anne (MDPI, 2023)
This paper investigates food system resilience—conceptualized through the four dimensions of agency, buffering, connectivity, and diversification—from the perspective of rural–urban relations. We consider three cases that capture distinct actor and policy foci in the wider literature on urban–rural interactions. These are secondary cities and their development potential as central nodes in urban–rural food systems, the role of digital infrastructure in shaping food systems resilience, and finally, street food vendors as a particularly vulnerable yet crucial group of actors linking rural food supply with urban demand. We review existing literature within these themes, with a particular focus on the impact of the COVID-19 pandemic on the food systems in middle- and low-income countries. This allows us to examine the relationship between rural–urban connectivity and food system resilience and to identify possible trade-offs. We formulate recommendations for research and policy around the notions of new localities (i.e., considering the interconnectedness of rural and urban food systems across administrative boundaries), smart development (i.e., context-specific approaches building on local strengths), and network governance (i.e., inclusive decision making engaging with diverse stakeholders across multiple scales).